ANALISIS MAKNA UNGKAPAN DALAM BAHASA GAUL DI BUNGKUSAN PERMEN “KIS” - Anita Zagoto (Jurnal Education and Development, 2021)
This research is motivated by the uniqueness found among teenagers and the expressions in the kis candy package, which are often used by teenagers to represent their feelings. which is a concern for various phenomena starting from the smallest things such as the expression contained in the kis candy package. Small things but can give meaning to others. Therefore, researchers conducted a study to find out what meanings contained in the kis candy package. With the aim of research to describe the meaning in slang contained in the kis candy package. By using a descriptive approach and method. The results of this study have been found by researchers that have data as many as 70 expressions contained in the candy kis package where the expressions are divided into several types of meanings, namely: (1) the emotive meaning contained in the candy package as many as 26 expressions (2) the pictorial meaning contained in the candy package. in the candy kis package as many as 26 expressions (3) the central meaning contained in the kis candy package as many as 18 expressions. Results Based on the research, it is recommended to: (1) It is recommended that today's teenagers understand a slang expression contained in candy packages and be able to give meaning according to the context. (2) It is suggested to the reader to understand the meaning of the word. (3) It is recommended to kis candy product companies that the expressions contained in the candy packages should not be the same in every single package.